Colorectal adenoma presence is associated with decreased menaquinone pathway functions in the gut microbiome of patients undergoing routine colonoscopy - Ilona Vilkoite; Ivars Silamiķelis; Jānis Kloviņš; Ivars Tolmanis; Aivars Lejnieks; Elīna Runce; Krista Cēbere; Ksenija Margole; Olga Sjomina; Laila Silamiķele (PLoS ONE, 2026)
Background Colorectal adenomas are key precancerous lesions and a major target for colorectal cancer prevention. While gut microbiome alterations are well described in colorectal cancer, microbial composition and functional capacity at the adenoma stage remain poorly understood. Emerging metagenomic data suggest early adenomas are associated with loss of microbial metabolic functions supporting epithelial and immune homeostasis. Objectives To investigate the association between gut microbiome composition and functional pathways and the presence of colorectal adenomas in patients undergoing routine colonoscopy. Materials and methods This cross-sectional case–control study included adult patients undergoing routine colonoscopy. Participants were enrolled based on strict inclusion and exclusion criteria to minimize confounding factors such as inflammatory bowel disease, prior colorectal surgery, and recent antibiotic or probiotic use. Fecal samples were collected prior to bowel preparation, and gut microbiome taxonomic composition and functional pathways were analyzed using shotgun metagenomic sequencing. Results A total of 136 participants were included, of whom 56 had colorectal adenomas. Alpha diversity indices did not differ significantly between adenoma-positive and adenoma-negative groups. In contrast, beta diversity analysis revealed significant differences in overall microbial community structure. Descriptive genus-level differences suggested features of dysbiosis in adenoma-positive patients, including higher relative abundance of Bacteroides and Prevotella and lower abundance of Faecalibacterium and Anaerostipes . Differential abundance analysis identified a single species-level feature, UBA7597 sp003448195, enriched in the adenoma group. Functional profiling showed reduced microbial pathways related to menaquinone (vitamin K₂) biosynthesis, Stickland fermentation, and short-chain fatty acid (propionate) production in patients with adenomas. Conclusions The presence of colorectal adenomas was associated with reduced microbial metabolic functions linked to vitamin K₂ biosynthesis, amino acid fermentation, and propionate production, alongside compositional shifts toward a less functionally robust gut microbiome. These findings indicate that early colorectal neoplasia is accompanied by functional microbiome alterations that may serve as markers of adenoma-associated dysbiosis and provide insight into early metabolic changes in the colonic microenvironment.